Malaysia : Report on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report, 2013)
This report is an assessment of the state of compliance with the Basel Core Principles (BCPs) in Malaysia. Bank Negara Malaysia (BNM) employs a well-developed risk-focused regulatory and supervisory system, consisting of a hands-on and comprehensive program of onsite supervision and extensive offsite macroeconomic and microeconomic surveillance supervision. The assessment has revealed several opportunities for improvement of the regulatory and supervisory framework. The Executive Board recommends the new financial services legislation, the Financial Services Act (FSA), to address many of these gaps.